Volume 1: 36th Design Automation Conference, Parts a and B 2010
DOI: 10.1115/detc2010-29068
|View full text |Cite
|
Sign up to set email alerts
|

Concept Opportunity Diagrams: A Visual Modeling Method to Find Multifunctional Design Concepts

Abstract: A transforming product is a system that has different functionality when physically changed or reconfigured into a different state. This increased functionality allows diverse customer needs to be met in a single product. Transforming devices have become more prevalent in recent years, as customers desire both increased capabilities and reduced complexity to reduce waste in our society. When designing a multifunctional product that transforms from one state to another, it can be difficult to conceptualize a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Transformation in mechanical products provides unique benefits that products otherwise cannot, e.g., an umbrella that folds to enhance portability, an aircraft that changes its wing shape to adapt to different modes of flight. A number of design researchers (Singh et al 2009, Camburn et al 2010, Kuhr et al 2010) have examined existing transformable products and developed techniques to assist in designing transformable products. In particular, Singh et al (2009) examined transformation in biological systems and were able to draw analogies between transformation in nature and engineering products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformation in mechanical products provides unique benefits that products otherwise cannot, e.g., an umbrella that folds to enhance portability, an aircraft that changes its wing shape to adapt to different modes of flight. A number of design researchers (Singh et al 2009, Camburn et al 2010, Kuhr et al 2010) have examined existing transformable products and developed techniques to assist in designing transformable products. In particular, Singh et al (2009) examined transformation in biological systems and were able to draw analogies between transformation in nature and engineering products.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al also identified analogous biological phenomena for each principle and facilitator. Camburn et al (2010) and Kuhr et al (2010) developed techniques and tools to support the design of transformable products. Camburn et al (2010) derived a set of indicators to identify when implementing transformation in products may be beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], the transformation design is refined to be simpler, easier to learn and follow, and more effective in drawing out untapped potential from the design process. In addition, a research presents a twofold process known as the Transformer Diagram Matching Method and shows the results on a fully functioning prototype of an office supply transformer [2]. The process takes transformation design methodology a large step forward by bridging its two ways of design together, directive and intuitive.…”
Section: Introductionmentioning
confidence: 99%
“…But few computational tools are specialized for the multifunction product. Therefore, it is more and more important to specially investigate the design approach of the multifunction product [1,2]. The multifunction product is defined as complex function product by Feng et al [3].…”
Section: Introductionmentioning
confidence: 99%